2021
DOI: 10.56499/jppres21.1078_9.5.746
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic approach of hydroxyapatite and polymethylmethacrylate composite exploration as dental implant biomaterial

Abstract: Context: The most common biomaterial used for dental implants is titanium. However, the release of metal ions and the risk of allergic reactions to metals that may occur in some patients cannot be avoided. Hydroxyapatite-polymethylmethacrylate (HA-PMMA) composite biomaterials are proposed to have potential as dental implant biomaterials due to their mechanical, chemical, and biological properties. HA-PMMA may induce osseointegration, biocompatible, less allergic reactions, and no metal ions released. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…29 The bond affinity value that used in this study is the smallest because it indicates the presence of additional stability and higher inhibition activity performed by the ligand towards the protein target. 30,31 The presence of bond types, amino acids on the active side, and amino acid residues on the ligands affects the affinity of the bond between the ligands and receptors. 12 The more hydrogen bonds, the more stable the ligand-protein interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The bond affinity value that used in this study is the smallest because it indicates the presence of additional stability and higher inhibition activity performed by the ligand towards the protein target. 30,31 The presence of bond types, amino acids on the active side, and amino acid residues on the ligands affects the affinity of the bond between the ligands and receptors. 12 The more hydrogen bonds, the more stable the ligand-protein interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The negative binding energy generated by hydrogen bonds aids stabilizes the binding between luteolin and TMPRSS2. 30 Pi-pi T shaped interaction is the interaction of electron pi clouds between two aromatic groups in the form of T. 34 The presence of pi-pi T shaped interaction affects the protein stability and flexibility and is important in drug intercalation and supramolecular chemistry. 35,36 PLpro has catalytic triads and important catalytic residues.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds cause the resulting binding affinity to be more negative, thus stabilizing the interaction of myricetin and ellagic acid with the SARS-CoV-2 RBD spike. 34 Furthermore, the presence of weak hydrophobic interactions such as Pi-alkyl, Pi-sigma, and vdw bonds aids the stability and turnover of interactions between ligands and target proteins in cellular processes. 35 SARS-CoV-2 helicase is involved in RNA replication.…”
Section: Resultsmentioning
confidence: 99%
“…The screening docking method is used to determine the activity of the ligand against the target protein by referring to the binding affinity produced (Ramadhani et al, 2022). Weak binding interactions are formed when the ligand binds to the target protein domain to contribute to triggering a biological response (Prahasanti et al, 2021). The results showed that the type of chemical interaction formed consisted of hydrogen, van der Waals, pi, and alkyl.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structure of the protein-ligand complex was displayed using the PyMol 2.5 version software. Proteins were displayed through the structure of cartoons and transparent surfaces, while sticks for ligands were selected for staining on both molecules (Prahasanti et al, 2021).…”
Section: Molecular Visualizationmentioning
confidence: 99%